Argasid Ticks of Palearctic Bats: Distribution, Host Selection, and Zoonotic Importance - Sándor, Attila D.; Mihalca, Andrei Daniel; Domşa, Cristian; Péter, Áron; Hornok, Sándor (Frontiers in Veterinary Science, 2021)
The soft ticks (Ixodida: Argasidae) are ectoparasites of terrestrial vertebrates with a wide geographic distribution, occurring on all continents. These ticks are obligate blood-feeders, most of them show high degrees of host-specialization and several species in arid and tropical regions are important parasites of livestock and men. Species commonly occurring on domestic animals and man are generally well known, with many studies focusing on their ecology, distribution or vectorial role. However, wildlife-specialist soft ticks are less studied. Nearly half of all soft tick species are bat specialists, with six species (Argas boueti, A. confusus, A. transgariepinus, A. vespertilionis and Ornithodoros salahi) occurring in the Western Palearctic. There is no comprehensive study on the distribution, hosts or pathogens in these soft ticks, although most species were shown to carry several viral, bacterial or protozoan pathogens and also to occasionally infest humans. Based on a literature survey and 1120 distinct georeferenced records, we present here the geographical range, host selection and vectorial potential for bat-specialist soft ticks occurring in the Western Palearctic (chiefly Europe, North Africa and the Middle East). Argas vespertilionis shows the largest distribution range and was found on most host species, being ubiquitous wherever crevice-roosting bats occur. All the other species were located only in areas with Mediterranean climate, with A. boueti, A. confusus and O. salahi are missing entirely from Europe. These three species have a host spectrum of bats roosting primarily in caves, while A. transgariepinus and A. vespertilionis is feeding primarily on crevice-roosting bat species. All but one of these soft tick species are known to feed on humans and may be vectors of important disease agents (Rickettsia spp., Borrelia spp., Bartonella spp., Ehrlichia spp., Babesia spp., several nairo- and flaviviruses). As several crevice-roosting bat species show a continuous adaptation to human-altered areas, with certain species becoming common city-dwellers in the Western Palearctic, the study of bat specialist soft ticks is also important from an epidemiologic point of view.